Pengaruh Model Pembelajaran Teams Games Tournament dan Motivasi Belajar Terhadap Retensi Kognitif Peserta Didik Sekolah Dasar - Rahmawati, Juana; Suswandari, Suswandari; Irdalisa, Irdalisa (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This research examines the influence of the TGT model and learning motivation on the cognitive retention of class IV students in social studies subjects at SDN Ragunan 01. This research uses a quantitative approach with an experimental method of 2x2 factorial design. Based on the results of hypothesis testing and data analysis, it can be concluded that 1) there is an influence of learning models on students' cognitive retention in social studies subjects; 2) there is an influence of learning motivation on increasing students' cognitive retention; and 3) there is an interaction effect between learning models and learning motivation on cognitive retention in social studies subjects. So, the TGT model and learning motivation influence the cognitive retention of class IV students in social studies subjects at SDN Ragunan 01.